(untitled) (Jurnal Legislatif, 2024)
The existence of regulations in the form of law is a real means of social control. This applies in the economic field, especially regarding electronic systems used by many parties. In the hierarchy, there are ministerial regulations that are widely used, one of the most recent is Minister of Trade Regulation No. 31/2023 concerning Business Licensing, Advertising, Guidance and Supervision of Business Actors in Trading via Electronic Systems. This regulation was formed as a reaction to the freedom in electronic trade, which caused an imbalance in conventional trade, especially domestic products. This research aims to review judicially the Minister of Trade Regulation No. 31/2023, which has been ratified. This research applied a normative method that placed law as the norm system. The norm system here is the principles, norms, rules of legislation. This regulation was chosen because of the great urgency for society and whether its existence harms the constitutions of other parties. Therefore, the author concludes, firstly, that in making Minister of Trade Regulation, it is necessary to involve the community actively as participants in carrying out the analysis. Secondly, this regulation has a big impact on the economy that requires re-adaptation for several elements of society. As expected, the Regulation of the Minister of Trade No. 31/2023 will be an appropriate solution to handle the current economic problem in Indonesia